The Relationship between Academic Achievement and the Emotional Well-Being of Elementary School Children in China: The Moderating Role of Parent-School Communication - Lv, Bo; Zhou, Huan; Guo, Xiaolin; Liu, Chunhui; Liu, Zhaomin; Luo, Liang (Frontiers in Psychology, 2016)
The relationship between academic achievement and the subjective well-being of elementary school children has received increasing attention. However, previous research on the relationship between these variables has yielded inconsistent conclusions – possibly due to the presence of potential moderating variables. This study investigated the relationship between the academic achievement and the emotional well-being (positive and negative affect) of elementary school children in China and the moderating effect of parent-school communication on this relationship. A total of 419 elementary school students and their parents participated. The elementary students’ positive and negative affect, their academic achievement on both midterm and final examinations of the most recent semester, and the frequency of parent-school communication were assessed. Academic achievement of elementary students was positively correlated with positive affect and negatively correlated with negative affect. Parent-school communication significantly moderated this relationship. Regardless of positive or negative affect, the correlation was only significant in the high parent-school communication group (one standard deviation higher than the mean) and in the mean group, whereas in the low parent-school communication group, no association was observed. These results indicate that parental engagement with school impacts both the academic achievements and subjective well-being of children in China.